2014
DOI: 10.1007/s11084-014-9365-6
|View full text |Cite
|
Sign up to set email alerts
|

Search for the Most ‘primitive’ Membranes and Their Reinforcers: A Review of the Polyprenyl Phosphates Theory

Abstract: Terpenoids have an essential function in present-day cellular membranes, either as membrane reinforcers in Eucarya and Bacteria or as principal membrane constituents in Archaea. We have shown that some terpenoids, such as cholesterol and α, ω-dipolar carotenoids reinforce lipid membranes by measuring the water permeability of unilamellar vesicles. It was possible to arrange the known membrane terpenoids in a ‘phylogenetic’ sequence, and a retrograde analysis led us to conceive that single-chain polyprenyl phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…This is also supported by the broad presence of CDP-alcohol phosphatidyltransferases, which catalyze the addition of polar headgroups (serine, glycerol, and myo-inositol) to produce intact phospholipids in both prokaryotic domains (60 -62), and suggests that at least one ancestor of CDP-based phospholipid synthesis was present in the LUCA (10,62,63). Biochemical and phylogenomic analyses have suggested that isoprenoids and fatty acid synthesis genes might have been present in the LUCA (10,50,64). However, a recent extensive phylogenomic analysis of the presence of fatty acid synthesis genes in Archaea contradicts the latter suggestion, instead indicating that in those archaea containing fatty acid synthesis genes (a chimeric pathway with both bacterial-like and archaeal genes) most of the genes were likely acquired from bacteria (65).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is also supported by the broad presence of CDP-alcohol phosphatidyltransferases, which catalyze the addition of polar headgroups (serine, glycerol, and myo-inositol) to produce intact phospholipids in both prokaryotic domains (60 -62), and suggests that at least one ancestor of CDP-based phospholipid synthesis was present in the LUCA (10,62,63). Biochemical and phylogenomic analyses have suggested that isoprenoids and fatty acid synthesis genes might have been present in the LUCA (10,50,64). However, a recent extensive phylogenomic analysis of the presence of fatty acid synthesis genes in Archaea contradicts the latter suggestion, instead indicating that in those archaea containing fatty acid synthesis genes (a chimeric pathway with both bacterial-like and archaeal genes) most of the genes were likely acquired from bacteria (65).…”
Section: Discussionmentioning
confidence: 90%
“…2D). The only regions of poorly defined side chain density are solvent-exposed and not associated with the active site (Glu 54 -Lys 64 and Arg 115 -Gln 116 ). G1PDH possesses two distinct structural domains separated by a deep binding cleft occupied by NADPH, substrate (or product), a single K ϩ (binary and ternary complexes only), and at the center Zn 2ϩ .…”
Section: Resultsmentioning
confidence: 99%
“…This broad definition—without any specification of the “features” the protocell should have had—leaves room for proposing many different types of protocell model systems [ 6 , 21 , 30 ]. They range from completely inorganic structures to aggregates of macromolecules and polymolecular assemblies of amphiphiles, whereby vesicular compartments—formed from potentially prebiotic lipidic amphiphiles [ 6 , 20 , 31 , 32 , 33 , 34 ], peptides [ 10 , 35 ], inorganic nanoparticles [ 36 , 37 ], or polysaccharides [ 38 ]—are of particular interest since the morphology of vesicles resembles most closely that of cells.…”
Section: Models For Prebiological Compartmentalizationmentioning
confidence: 99%
“…The presence of other amphiphiles with functional headgroups (phosphate, phosphonate, and amine/ammonium) can be also inferred: Traces of short alkyl chains with a functional group containing phosphorus or nitrogen [ 85 , 86 , 87 ] have been found in meteorites even though these particular molecules cannot assemble into structures by themselves. Prebiotic syntheses of phosphate amphiphiles have been proposed [ 33 , 98 ] that are plausible under prebiotic conditions, e.g . , using simple alkanols as precursors, ammonium hydrogen phosphate as reactant and urea as a catalyst under dehydrating conditions (100 °C).…”
Section: Sources Of Potentially Prebiotic Compartment Building Blomentioning
confidence: 99%
“…It has been argued that terpenes (and not LCFAs) were the essential components of primitive membranes (Ourisson 1989, Ourisson & Nakatani 1994, Nakatani et al 2012, as well as those of present-day Archaea (Langworthy et al 1982). Indeed, polyprenyl phosphates spontaneously form membrane vesicles (Nakatani et al 2014). That these molecules are the functional equivalents of LCFAs was elegantly demonstrated by the engineering of E. coli whose membranes contain up to 30% of archaeal lipids -these bacteria are viable, and under some conditions the hybrid membrane even confers a growth advantage (Caforio et al 2018).…”
Section: Life and The Great Oxygenation Event (Goe)mentioning
confidence: 99%